2021
DOI: 10.3390/ijms22062786
|View full text |Cite
|
Sign up to set email alerts
|

Medically Important Alterations in Transport Function and Trafficking of ABCG2

László Homolya

Abstract: Several polymorphisms and mutations in the human ABCG2 multidrug transporter result in reduced plasma membrane expression and/or diminished transport function. Since ABCG2 plays a pivotal role in uric acid clearance, its malfunction may lead to hyperuricemia and gout. On the other hand, ABCG2 residing in various barrier tissues is involved in the innate defense mechanisms of the body; thus, genetic alterations in ABCG2 may modify the absorption, distribution, excretion of potentially toxic endo- and exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 224 publications
0
8
0
Order By: Relevance
“…ABCG2 also plays a key role in protecting hematopoietic stem cells from low-oxygen environments and cytotoxins 2 , 3 . Further, genetic variation of ABCG2 is associated with increased risk of gout and hyperuricemia due to ABCG2 transport of the endogenous substrate uric acid 4 . Understanding the factors contributing to the interactions between ABCG2 and its substrates/inhibitors will provide a basis for the rational development of advanced therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…ABCG2 also plays a key role in protecting hematopoietic stem cells from low-oxygen environments and cytotoxins 2 , 3 . Further, genetic variation of ABCG2 is associated with increased risk of gout and hyperuricemia due to ABCG2 transport of the endogenous substrate uric acid 4 . Understanding the factors contributing to the interactions between ABCG2 and its substrates/inhibitors will provide a basis for the rational development of advanced therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the localization of these polymorphisms on the protein sequence of ABCG2 is shown in Figure 1. It should be noted that there is a subset of other function-impairing SNPs in ABCG2 [95,96], but most of them have not yet been associated with pediatric hyperuricemia or early-onset gout. One of the best-studied variations of the ABCG2 amino acid sequence is the previously discussed Q141K polymorphism, which also gives rise to other important clinical phenotypes, such as in the pharmacokinetics and tissue distribution of drugs transported by ABCG2 [97].…”
Section: Abcg2 Polymorphisms In Pediatric-onset Hyperuricemia and Early-onset Goutmentioning
confidence: 99%
“…In contrast, the Q141K and Q126X polymorphisms are enriched in Japanese populations, whereas in Caucasians, Q141K is not as common and Q126X is virtually absent [97]. Our understanding of the genetic variations in the ABCG2 sequence associated with hyperuricemia and gout is still incomplete, as evidenced by the recent discovery of less common polymorphisms previously unrecognized or not studied in the context of hyperuricemia and gout [89,90,95,100]. Two of these newly identified rare polymorphisms have been recently described in a case report of a 12-year-old Czech girl of Roma ethnicity with chronic asymptomatic pediatric-onset of hyperuricemia [89].…”
Section: Abcg2 Polymorphisms In Pediatric-onset Hyperuricemia and Early-onset Goutmentioning
confidence: 99%
“…Since it has subspecies polyspecificity and is present in many tissues, protein is an important factor in resistance to therapy [ 170 , 171 , 172 ]. In some tumor formations, ABCG2 is strongly overexpressed, which is correlated with unfavorable clinical outcomes for these tumors [ 173 ]. Because the carrier is crucial for the pharmacokinetics of certain compounds, the US Food and Drug Administration and European Medicines Agency have indicated that pharmacokinetic studies and drug–drug interactions have been performed for it [ 174 ].…”
Section: Flavonoidsmentioning
confidence: 99%